Negative aspects of the information society development - Stanislaw Ślusarczyk; Kamila Wrzesińska (Economic and Environmental Studies (E&ES), 2018)
The development of an information society leads to a shift from material civilization towards an invisible civilization which should properly be called an information civilization. The information civilization creates enormous opportunities for society and economy. Internet-based functions, such as teleworking, tele-education or tele-information have their social and economic implications. Goal of the article: The goal of the study is to draw attention to the social consequences of the fast development of the information society with a presentation of selected threats to children and young people in cyberspace. Methodology: The study uses the research method based on the literature analysis of the phenomenon of threats to children and adolescents in cyberspace, results of research conducted among others by the Nobody's Children Foundation and the Central Statistical Office of Poland. Conclusions: Wide perception of the cyberbullying problem is needed as this issue concerns children and young people as well as parents and teachers.
Keywords: Z13; 330; information society; cyberbullying; sexting; grooming